Variasi Pecahan Biji Jagung (Zea mays) sebagai Nutrisi terhadap Pertumbuhan Misellium Jamur Tiram (Pleurotus ostreatus) - Zulkarnain, Kadri; Siswanti, Eka (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2022)
In the cultivation of oyster mushroom seeds, there are still many who do not understand how to make oyster mushroom seeds properly. Some alternative ways of making oyster mushroom seeds are by breaking corn seeds as nutrients for oyster mushroom seeds. The increasing demand for fresh mushrooms requires farmers to be able to speed up the process of making oyster mushroom (Pleurotus ostreatus) seedlings. One alternative to speed up seeding is with corn seeds. Corn kernels are known as one of the ingredients for making oyster mushroom seeds. Corn seed size is thought to affect the growth of oyster mushroom mycelium. The aims of this study were (1) to determine the effect of different fractions of corn kernels (Zea mays) as a medium for making oyster mushroom (Pleurotus ostreatus) seeds; (2) To determine the growth media for oyster mushroom (Pleurotus ostreatus) seedlings on the growth of mycelium. This type of research is pure experiment. This study used a completely randomized design (CRD) with 5 treatments each with 4 replications, namely whole corn, coarse corn kernels (3.5mm diameter), fine corn kernel fraction (1.6 mm diameter), finer corn kernel fraction (diameter 0.4 mm) and corn flour, each soaked in 1 liter of water with 5% sugar content. Parameters observed were mycelium length, thickness and color. Data analysis used ANOVA (Analysis Of Variance) with the following results 0223 < 0.05.